L'enseignement du chinois dans une classe hétérogene - Zhang-Fernandez, Rong (Linguistica (Ljubljana), 2014)
The heterogeneous nature of the Chinese classroom is a reality in the teaching of Chinese in France, both in secondary and higher education. This heterogeneity is due to several reasons: different levels of language knowledge, different origins and backgrounds of the students, different teaching/learning objectives, different cultural and family background, and social factors. Our research has been conducted in a final-year LIE college class (langue inter-établissement;) in a French secondary school. In our study, the following questions have been posed: How to best adapt the teaching of Chinese to fit the needs of all students? Would differentiated instruction be a solution? What would be the best strategies and practices, in view of the CEFR requirements related to teaching content, to tasks and to assessment? Taking into account a detailed analysis of the class in question in terms of the type of students, the differences in their knowledge of language, and their learning goals, , we adopt the theory of differentiated instruction - its main ideas strategies, its overall methodology and practical techniques to address the difficulties ensuing from classroom heterogeneity. The differentiation is implemented at the level of content, task selection, course structure and evaluation. Are there any limitations to differentiated instruction? Strong discrepancies in the levels of students' knowledge is potentially a problem, and differences in their work pace as well as the teachers' increased workload can also present difficulties. New ways of organizing language classes such as grouping students on the basis of their various language skills could help solve these issues.
Keywords: apprenants français; chinois; didactique des langues; didaktika jezika; diferencirani pouk; enseignement des langues; francoski učenci; kitajščina; pédagogie différenciée; poučevanje jezika; tuji jeziki